Journalist Perceptions and Views towards the Integration of AI-based Applications in the Journalism Industry in Pakistan: Expansion of the UTAUT Model - Shah, Masoomi Hifazat Ali; Khoso, Ikhtiar Ahmed; Dharejo, Nasrullah (Annals of Human and Social Sciences, 2024)
The study aims to identify the factors influencing the integration of AI-based applications in the journalism industry and understand the journalists’ concerns. Related work revealed many journalists may fail to utilize AI-based tools effectively in their media routine tasks. Conversely, AI algorithms may give rise to privacy issues being incorporated into news coverage may decline credibility amongst audiences. In this context, UTAUT model was applied to determine the influential factors. For the quantitative approach, a survey questionnaire was devised to validate the research model and achieve research objectives. Thirty-nine participants recorded initial responses for the reliability analysis. The reliability test (Cronbach's Alpha) was applied and all constructs exhibited significant results higher than 0.7 deemed reliable, ranging from 0.782 to 0.902. The integration of AI applications in journalism industry research offers valuable contributions by enhancing efficiency, accuracy, and collaboration, ultimately advancing the quality and impact of research outcomes in the field.